Effectiveness of Antiresorptive Treatment on Formation of Nonvertebral Fracture in Old Age: A Retrospective Study - Hakan Tuna; Ferda Özdemir; Coşkun Zateri; Hatice Gül; Siranuş Kokino (Galenos Yayinevi, 2005)
Getting longer mean life span has made old population increase, and the risk of fracture is increased in women due to senile osteoporosis added on postmenopausal osteoporosis. It is known that this situation causes an significant increase in cost of health care and disability in elderly women. In this study we investigated whether there are differences in new nonvertebral fractures between two groups using and not using antiresorptive treatment. In both groups risk factors were equally distributed. The first group was composed of 64 women who had been using antiresorptive treatment for 3 to 5 years, the mean age of whom was 63.7, and the second group was composed of 28 women who had never used antiresorptive treatment with the mean age of 62.7. In all regions except for femur neck t scores, statistically significant low values had been determined in the group which had not used antiresorptive treatment. The fact that fracture was high in the group not using antiresorptive treatment was found to be statistically significant. This study in which we aimed to determine the relation between values of DEXA and fracture in groups using and not using antiresorptive treatment showed that antiresorptive treatment prevented formation of fracture.